Case report: Characterization of the immunologic and molecular landscape in a unique presentation of invasive lobular carcinoma with concurrent uterine carcinosarcoma treated with immunotherapy - Riedinger, Courtney J.; Eisele, Caprice D.; Esnakula, Ashwini; Stover, Daniel G.; Freud, Aharon G.; Cosgrove, Casey M. (Frontiers in Immunology, 2024)
Invasive lobular breast cancer (ILC) is characterized by a relatively high risk for late recurrence and a unique metastatic pattern with an increased risk for metastasis to gynecologic organs and peritoneum.We present a unique case of recurrent ILC with metastasis to the abdominal peritoneum as well as the uterine myometrium and cervix. Treatment was complicated by the discovery of concomitant uterine carcinosarcoma. This patient was effectively treated with a combination of hormonal therapy for her metastatic ILC and a combination of chemotherapy and immunotherapy for uterine carcinosarcoma.Molecular evaluation revealed a characteristic CDH1 mutation within the ILC and a PI3KCA mutation within the uterine carcinosarcoma, both of which have been linked to epithelial-to-mesenchymal transitions. Examination of the tumor immune microenvironment revealed proportionally more cytotoxic NK cells. This robust immune infiltration may be an indicator of the response to immunotherapy observed in this tumor or a result of the metastatic breast cancer within the uterus. This report provides a characterization of the molecular and immunologic landscape in this case with metastatic ILC and uterine carcinosarcoma. Introduction: Invasive lobular breast cancer (ILC) accounts for 5-15% of breast cancer cases [1]. Loss of Ecadherin expression via the CDH1 gene is a hallmark of ILC and has been associated with epithelial-to-mesenchymal transition [2]. ILC has a relatively high risk for late recurrence [3] with an increased frequency of involvement of bone, gastrointestinal sites, gynecologic organs, and peritoneum [4,5]. When breast cancer metastasizes to gynecologic organs, the ovaries are the most frequent metastatic site, and the uterus and cervix are rarely involved [6][7][8]. We report a rare case of lobular breast cancer metastatic to the uterus and cervix which was discovered